2020
DOI: 10.1186/s12893-020-00785-w
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-visceral fat CT value ratio and serrated pancreatic contour are strong predictors of postoperative pancreatic fistula after pancreaticojejunostomy

Abstract: Background: Our aim is to elucidate the true preoperative risk factors for postoperative pancreatic fistula (POPF) after pancreaticoduodenectomy (PD), making it possible to select POPF high-risk patients preoperatively regardless of intraoperative pancreatic consistency judged by the surgeon's hand. Methods: Among the 298 patients who underwent PD with pancreaticojejunostomy from 2007 to 2016, 262 patients had preoperative CT configurations that could be precisely evaluated. Risk factor analyses were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In recent years, some studies have confirmed that that preoperative CT scans have the value of predicting POPF [ 21 , 22 ], and some research suggested that the number of CT scans of the pancreas was related to the density of the pancreas and suggested pancreatic fibrosis [ 23 , 24 ]. In addition, Kusafuka et al reported that a pancreas-visceral fat CT value ratio ≥ – 0.40 and a serrated-type pancreas might indicate a high risk of POPF [ 14 ]. To standardize the judgement of pancreatic texture, the preoperative plain CT scan was chosen as the index in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, some studies have confirmed that that preoperative CT scans have the value of predicting POPF [ 21 , 22 ], and some research suggested that the number of CT scans of the pancreas was related to the density of the pancreas and suggested pancreatic fibrosis [ 23 , 24 ]. In addition, Kusafuka et al reported that a pancreas-visceral fat CT value ratio ≥ – 0.40 and a serrated-type pancreas might indicate a high risk of POPF [ 14 ]. To standardize the judgement of pancreatic texture, the preoperative plain CT scan was chosen as the index in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some research groups have extensively analyzed CT images of the pancreas and have identified many variables that are significantly associated with POPF [ 12 14 ]. The diameter of the main pancreatic duct (MPD) and the CT value of the pancreatic body are the independent components derived from CT images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 30-day and in-hospital mortality rates were reported to be 1.2% and 2.8%, respectively, according to Japan's National Clinical Database [1]. However, postoperative pancreatic fistula (PF) is still a significant threat to both patients and pancreatic surgeons because it sometimes causes fatal postoperative intra-abdominal bleeding [2,3] and abscess [4,5], and its incidence is still reported to be high (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).4%) in patients with soft pancreas [6][7][8]. Therefore, there is a need to elucidate the global preoperative risk factors for PF, and several studies have shown preoperative risk factors such as obesity, fatty pancreas, narrow pancreatic duct, male sex, and surgical techniques [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…30-day and in-hospital mortality rates were reported to be 1.2 and 2.8%, respectively, by national clinical database from Japan 1 . However, postoperative pancreatic stula (PF) is still a large threat to both patients and pancreatic surgeons, because it sometimes causes the postoperative fatal intraabdominal bleeding 2, 3 and abscess 4,5 , and its incidence is still reported to be high (11-29.4%) in patients with soft pancreas [6][7][8] . Therefore, it is urgent to elucidate the global preoperative risk factor of PF and there has been several articles showing the preoperative risk factors such as obesity, fatty pancreas, narrow pancreatic duct, male and surgical technics et al [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%